Representation of diabatic potential energy matrices for multiconfiguration time-dependent hartree treatments of high-dimensional nonadiabatic photodissociation dynamics - Han, Shanyu; Schröder, Markus; Gatti, Fabien; Meyer, Hans-Dieter; Lauvergnat, David; Yarkony, David R.; Guo, Hua (Journal of chemical theory and computation, 2022)
Conventional quantum mechanical characterization of photodissociation dynamics is restricted by steep scaling laws with respect to the dimensionality of the system. In this work, we examine the applicability of the multi-configurational time-dependent Hartree (MCTDH) method in treating nonadiabatic photodissociation dynamics in two prototypical systems, taking advantage of its favorable scaling laws. To conform to the sum-of-product form, elements of the ab initio diabatic potential energy matrix (DPEM) are re-expressed using the recently proposed Monte Carlo canonical polyadic decomposition method, with enforcement of proper symmetry. The MCTDH absorption spectra and product branching ratios are shown to compare well with those calculated using conventional grid-based methods, demonstrating its promise for treating high-dimensional nonadiabatic photodissociation problems.